Nonmarket networks among migrants: evidence from metropolitan Bangkok, Thailand - Yamauchi, Futoshi (International Food Policy Research Institute, 2003)
This paper examines nonmarket interactions among migrants from same origins in the urban labor market of Bangkok, Thailand. We test whether the labor-market performance of previous migrants has externalities to that of new migrants who moved from the same province of origin. Our empirical results, which control origin fixed effects, time-fixed effects, and origin/year-specific correlated shocks, show that (1) the relative size of the migrant population in the market decreases employment probabilities of new migrants (negative substitution effect), (2) the employment probability of previous migrants increases those of new migrants (positive externalities), and (3) when the employment probability of previous migrants approaches to unity, the size effect becomes positive, showing informational scale economies. The results imply that the positive informational scale effect dominates the negative substitution effect when the efficiency of previous migrants is sufficiently high in the labor market.